Clinical Outcome of First‐ vs Second‐Generation DES According to DAPT Duration: Results of ARCTIC‐Generation. Issue 4 (16th February 2016) - Collet, Jean‐Philippe; Silvain, Johanne; Kerneis, Mathieu; Cuisset, Thomas; Meneveau, Nicolas; Boueri, Ziad; Barthélémy, Olivier; Rangé, Grégoire; Cayla, Guillaume; Belle, Eric Van; Elhadad, Simon; Carrié, Didier; et al.
ABSTRACT: There is an apparent benefit with extension of dual antiplatelet therapy (DAPT) beyond 1 year after implantation of drug‐eluting stents (DES). Assessment by a Double Randomization of a Conventional Antiplatelet Strategy vs a Monitoring‐Guided Strategy for Drug‐Eluting Stent Implantation, and of Treatment Interruption vs Continuation One Year After Stenting (ARCTIC)‐Generation assessed whether there is a difference of outcome between first‐ vs second‐generation DES and if there is an interaction with DAPT duration in the ARCTIC‐Interruption study. ARCTIC‐Interruption randomly allocated 1259 patients 1 year after stent implantation to a strategy of interruption of DAPT (n = 624), in which aspirin antiplatelet treatment only was maintained, or DAPT continuation (n = 635) for 6 to 18 additional months. The primary endpoint was the composite of death, myocardial infarction, stent thrombosis, stroke, or urgent revascularization. A total of 520 and 722 patients received a first‐ and a second‐generation DES, respectively. After a median follow‐up of 17 months (interquartile range, 15–18 months) after randomization, the primary endpoint occurred in 32 (6.2%) and 19 (2.6%) patients with first‐ and second‐generation DES, respectively (hazard ratio: 2.31, 95% confidence interval: 1.31‐4.07, P = 0.004). This was observed irrespective of the strategy of interruption or continuation of DAPT and timing of study recruitment. Major bleeding events occurred in 4 (0.8%) and 3 patients (0.4%) with first‐ and second‐generation DES, respectively (hazard ratio: 1.79, 95% confidence interval: 0.40‐8.02, P = 0.44). Results did not change after multiple adjustments for potential confounding variables. ARCTIC‐Generation showed worse clinical outcome with first‐ vs second‐generation DES, a difference that appeared to persist even with prolonged DAPT.